2022
DOI: 10.3390/polym14204350
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Influence of Production Method, Plastic Content on the Basic Performance of Waste Plastic Modified Asphalt

Abstract: The sustainable reuse of waste plastic as an alternative construction material has numerous environmental and economic advantages. New opportunities to recycle waste plastic in asphalt for road construction would mitigate landfill issues and significantly reduce global carbon emissions. With a clear aim to contribute to a more efficient reuse of waste plastic, this paper reutilized two types of waste plastic (polypropylene (PP) and polyethylene (PE)) as asphalt modifiers to improve the performance of asphalt p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Moreover, asphalt containing PP and PE prepared by the orthogonal test was used to examine the mechanisms of dispersion and modification of plastic particles in modified asphalt. The outcomes showed that the modified samples showed better performance at high temperatures in comparison to the conventional asphalt sample [16]. Furthermore, the wet method has been used to assess the effects of adding different amounts of plastic cup.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, asphalt containing PP and PE prepared by the orthogonal test was used to examine the mechanisms of dispersion and modification of plastic particles in modified asphalt. The outcomes showed that the modified samples showed better performance at high temperatures in comparison to the conventional asphalt sample [16]. Furthermore, the wet method has been used to assess the effects of adding different amounts of plastic cup.…”
Section: Introductionmentioning
confidence: 99%
“…However, there has been a need for performance tests to ensure the satisfactory performance of the asphalt mixtures under in-service conditions [ 4 , 5 , 6 , 7 , 8 ]. A performance-based mix design (PBMD) determines the optimal proportions based on predicted performance, which balances competing demands for cracking and permanent deformation [ 9 , 10 ] because these two distresses are somewhat oppositely driven by the relative quantities of aggregate and asphalt binder [ 11 , 12 , 13 ]. This study suggests a PBMD framework that can support performance-related specification (PRS) required for the mathematic relationships between volumetric asphalt mix designs and predicted performance and develop a fatigue-preferred, rutting-preferred, performance-balanced mix designs that can reduce the critical structural distresses for long-life [ 7 , 11 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The PRS is a specification that describes the desired levels of key materials and construction quality characteristics that have been found to correlate with fundamental engineering properties that predict performance [ 15 ]. In order to support a PRS system, a PBMD framework can provide the mathematical models that explain the relationship between the acceptance quality characteristics (AQCs) and predicted performance for selected mixtures [ 2 , 11 , 12 , 16 ]. The volumetric and/or mechanical AQCs that can be measured during construction are also identified through the PBMD framework [ 1 , 7 , 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the recycling of waste materials has received increasing attention [ 1 , 2 , 3 , 4 ]. As the consumption of plastic products has increased, the amount of waste plastic has also increased [ 5 , 6 , 7 ]. It is estimated that the global production of waste plastics amounts to 300 million tons, but less than 20% of waste plastics are recycled.…”
Section: Introductionmentioning
confidence: 99%